Application problems of legislation on administrative offenses in the field of customs - Taitorina, B.A.; Baisalova, G.T.; Assanova, A.A. (Bulletin of the Karaganda University “Law Series”, 2020)
The work reveals the concept and features of the qualification of administrative offenses; the choice of administrative penalties applied to persons guilty of their commission is justified; The types of administrative responsibility for committing administrative offenses encroaching on the normal activities of customs authorities are identified. The authors revealed signs of the composition of violations of customs rules. The possibility of using some of them as classification criteria to determine the basis of administrative responsibility made it possible to identify the features of administrative tort, and at the same time, to form a specific type of classification of offenses. The authors of the article found that the specifics of administrative-legal coercion in case of violation of customs rules are determined by its following main features: 1) application mainly by customs authorities and their officials, as well as judges in the framework of relevant law enforcement relations; 2) the use of organizational and technical means to ensure its use; 3) application in administrative and jurisdictional activities of customs authorities, which goes beyond the scope of proceedings on administrative offenses; 4) the application of coercive measures mainly of a property nature; 5) close relationship with the forms of customs control. The study proposes a solution to legal and organizational problems arising from the application of administrative law enforcement in violation of customs regulations, taking into account the specifics of customs and administrative legislation.